Synthesis and characterization of new ferrocenyl and 3-methoxytolyl dithiophosphonates - SAĞLAM, ERTUĞRUL GAZİ (My University, 2022)
In this study, perthiophosphonic acid anhydrides which are previously synthesized (2,4-bis(3-methoxytolyl)-1,3-dithia-2,4-diphosphetane-2,4-disulfide ([((3-methoxytolyl)P(S)S)2], SAV-B1 reagent and 2,4-bis(ferrocenyl)-1,3,2,4-dithiadiphosphetane-2,4-disulfide [((ferrocenyl)P(S)S)2], FcLR, Ferrocenyl Lawesson's Reagent) react with alcohols to obtain new dithiophosphonic acids (3-methoxytolyl=(CH3)(OCH3)C6H3- and Xn=Alkyl group (R) for SAV-B1, HXn; R1=3-pentyl-, HX1; R2=2-butyl-, HX2; R3=2-pentyl-, HX3 and Fc=Ferrocenyl- and Yn=Alkyl or aryl group (R') for FcLR, HYn; R'1=4-tert-cyclohexyl-, HY1; R'2=2-phenyl-1-propyl-, HY2). These products were later transformed into their ammonium salts ([NH4][Xn], [NH4][Yn]). The structures of ammonium salts were characterized by mass, FT-IR, 1H-, 13C- and 31P-NMR spectroscopy and elemental analysis.
Keywords: Kimya; İnorganik Kimya; Koordinasyon Kimyası; Organometalik Kimya; Yeni Ligandlar; Temel Bilimler; Chemistry; Inorganic Chemistry; Coordination Chemistry; Organometallic Chemistry; Novel Ligands; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; KİMYA, İNORGANİK VE NÜKLEER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; CHEMISTRY, INORGANIC & NUCLEAR; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences